2008
DOI: 10.1007/s12160-008-9055-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Brief Image-Based Multiple-Behavior Intervention for College Students

Abstract: Background-Epidemiologic data indicate most adolescents and adults experience multiple, simultaneous risk behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 49 publications
2
69
0
Order By: Relevance
“…These results were small in size, with the exception of stopping drinking which was medium sized, suggesting the brief intervention might have its greatest effects for adolescents who are already drinking. These results support alcohol reductions found in previous brief integrative intervention trials, particularly among those adolescents already engaged in substance use (Werch et al, 2005; Werch et al, 2008b). While a reduction on cigarette smoking was also found among adolescents receiving the brief intervention, these effects were not significant because few adolescents in the study reported smoking cigarettes.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These results were small in size, with the exception of stopping drinking which was medium sized, suggesting the brief intervention might have its greatest effects for adolescents who are already drinking. These results support alcohol reductions found in previous brief integrative intervention trials, particularly among those adolescents already engaged in substance use (Werch et al, 2005; Werch et al, 2008b). While a reduction on cigarette smoking was also found among adolescents receiving the brief intervention, these effects were not significant because few adolescents in the study reported smoking cigarettes.…”
Section: Discussionsupporting
confidence: 89%
“…The Health and Fitness Survey (Werch et al, 2008b) was used to collect primary and secondary outcome measures. Measures used in this survey were adopted from those used in previous evaluations of brief multiple behavior interventions (Werch et al, 2007; Werch et al, 2008a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…three servings of vegetables per day in the vegetable world and can be played alone or against others in the community to promote motivation for behavior change through social comparison and competition [50,56]. In the drinking world, a sugar mountain builds up additionally, while tracking sugarsweetened beverages, which users must reduce through answering quiz questions before attacking the next challenge.…”
Section: Challengesmentioning
confidence: 99%
“…Inserting fictitious drug items into surveys has been a method utilized by substance use researchers (e.g., Petzel, Johnson, & McKillip, 1973;Sobell & Sobell, 1978) and epidemiologists (e.g., Werch et al, 2008) as well. Informatively, 3.8% of high school students studied by Petzel et al (1973) reported they had used a fictitious drug.…”
Section: Introductionmentioning
confidence: 99%